2020
DOI: 10.1039/d0cc05989g
|View full text |Cite
|
Sign up to set email alerts
|

Helical nanofibers of N-(perfluorooctanoyl)cysteine ethyl ester in coordination polymers of Ag+

Abstract: We propose to employ the formation of coordination polymers with Ag+ to probe the difference of perfluorinated alkyl chain from alkyl chain, by deriving into thiol ligand N-(perfluoroalkanoyl)cysteine. Quick formation...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…To induce the aggregation of a PA, a metal ion such as silver(I) must be added. The metal cation should form a PA/Ag + complex stabilized by Ag + •••π interactions, which can be extended to form a 1D metallosupramolecular polymer by the presence of argentophilic Ag + •••Ag + interactions between the metal ions [57][58] and the presence of π•••π interactions between different PAs (Scheme 1). Thus, the metal ion is needed to promote the self-assembly of the PA. Interestingly, functionalization of the PA with a chiral group should force the building blocks to rotate in a specific direction during the self-assembly to form either a P or an M metallo-supramolecular helix, which depends on the chirality of the pendant group.…”
mentioning
confidence: 99%
“…To induce the aggregation of a PA, a metal ion such as silver(I) must be added. The metal cation should form a PA/Ag + complex stabilized by Ag + •••π interactions, which can be extended to form a 1D metallosupramolecular polymer by the presence of argentophilic Ag + •••Ag + interactions between the metal ions [57][58] and the presence of π•••π interactions between different PAs (Scheme 1). Thus, the metal ion is needed to promote the self-assembly of the PA. Interestingly, functionalization of the PA with a chiral group should force the building blocks to rotate in a specific direction during the self-assembly to form either a P or an M metallo-supramolecular helix, which depends on the chirality of the pendant group.…”
mentioning
confidence: 99%
“…We have recently shown that the coordination polymers of Ag + with chiral thiol ligands exhibit interesting properties, [1][2][3][4][5][6][7][8][9][10] including overall supramolecular chirality with respect to the molecular and supramolecular chirality of the ligands, 6 properties consistent with their serving as functional materials for sensing, [1][2][3][4][8][9][10] and their being amenable to having their morphologies controlled. 7 We therefore considered extending these efforts to the study of aggregates of these coordination polymers, a subject not yet pursued despite the wealth of investigations on the aggregates of the covalent polymers. In this regard, it was critical to design a thiol ligand whose properties would be sensitive to the existing forms of the polymers.…”
mentioning
confidence: 99%